The effects of the COVID‐19 pandemic on French‐Canadian adolescents' academic motivation: A follow‐up study. Issue 9 (22nd September 2022) - Smith, Jonathan; Guimond, Fanny‐Alexandra; St‐Amand, Jérôme; Fitzpatrick, Caroline; Bergeron, Julie; Gagnon, Mathieu
Abstract: We previously shared results suggesting that the academic motivation of a sample of French‐Canadian adolescents remained stable from few weeks before the first wave to the second wave of the COVID‐19 pandemic. We here examine if this pattern persisted using data collected at a third time point.